Increased IgE Deposition in Appendicular Tissue Specimens Is Compatible with a Type I Hypersensitivity Reaction in Acute Appendicitis. (18th October 2021) - Carvalho, Nuno; Barros, André; Coelho, Hélder; Cóias, Ana; Botelho, Pedro; Cismasiu, Brigitta; Moita, Luís; Costa, Paulo
Abstract : Background . IgE mediates type I hypersensitivity reaction and can be found in the mucosa of organs affected by allergy. Acute appendicitis (AA) is a common disease, but its etiology remains poorly understood. Here, we investigated IgE deposition in histological sections of AA samples to test the hypothesis that an allergic reaction may substantially contribute to the pathophysiology of AA. Materials and Methods . In a retrospective study, we assessed the presence of IgE in appendicular specimens of histologically confirmed appendicitis and in the control group, comprised of negative appendicitis and incidental appendectomies, using a monoclonal antibody against human IgE. Samples from 134 appendectomies were included: 38 phlegmonous and 27 gangrenous appendicitis from the study group and 52 incidental appendectomies and 17 negative appendicitis from the control group. The slides were visualized by light microscopy, and a standard procedure was used to manually count the positive IgE staining cells. Results . IgE staining was present in the cells of all but 5 appendicular specimens. We found a significantly increased number of IgE-positive cells in phlegmonous AA (median = 28 ) when compared to incidental appendectomy (median = 17 ) (p = 0.005 ; p < 0.0001 when adjusted for age and gender). No difference was found for gangrenous appendicitis. Discussion . The presence of IgE supports the contribution of an allergic reaction for the pathophysiology of phlegmonous appendicitis. The reduced number of IgE staining cells in gangrenous appendicitis can be due to tissue destruction, or, as been claimed by others, gangrenous appendicitis is a distinct entity, with different etiology. Conclusion . In this study, phlegmonous appendicitis had the highest number of IgE-positive appendicular cells. These findings suggest that an allergic reaction can contribute to the pathophysiology of AA, opening a novel possibility for preventive measures in a disease that typically requires surgery.